Achieving sustainable industrial ecosystems by design: A study of the ICT and electronics industry in Taiwan - Suppipat, Suphichaya; Hu, Allen H. (Journal of cleaner production, 2022)
The environmental and economic aspects of sustainability have been the most common subjects in the manufacturing industry, while the social one tends to be neglected. The process of semistructured interviews is conducted with design practitioners in the computer, communication, and consumer electronics industry in Taiwan to comprehend how the participating companies can move from a business-as-usual model to a more sustainable business by design. Results show that ecodesign and design for circular economy are commonly applied as sustainable design strategies, highlighting the concept of dematerialization. The three pragmatic tools applied alongside for balancing the three pillars of sustainability are life cycle thinking, design thinking, and business model tools. To achieve sustainable industrial ecosystems, three key actors, namely, a driver, a facilitator, and a supporter, play an important role to create stakeholder engagement and supply chain collaboration. Hence, the companies must tackle major challenges related to organizational culture, social reputation and communication, resource availability, service at the end of life, and effective waste treatment. Relying solely on product level for sustainability is insufficient; the companies need to tap into socio-technical systems by creating new partnerships, supporting multidisciplinary teams, embracing new markets, integrating emerging technologies for social sustainability, and promoting innovative and social inclusive thinking. •External drivers foster design for sustainability of the enterprises in Taiwan.•Ecodesign and circular design are commonly applied in transition to sustainability.•A systematic and human-centric approach is needed to enhance social sustainability.•Business model, LCA-based, and design thinking tools are used in practice.•Three key actors in sustainable industrial ecosystems are described.